Pendampingan Etika Bisnis Syariah pada UMKM Beauty Lily Collection Kecamatan Jambangan Kota Surabaya - Mutmainnah, Dewi; Syahrenny, Nenny; Fitria, Astri (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
Sharia Business Ethics Assistance at Beauty Lily Jambangan Surabaya is a community service program that aims to help Beauty Lily Jambangan Surabaya in applying Sharia business principles and developing their business. This program was implemented to increase awareness and understanding of Sharia business ethics, as well as help Beauty Lily Jambangan Surabaya adapt to challenges during the COVID-19 pandemic. The method of implementing this program includes the planning, training, and mentoring stages, as well as monitoring and evaluation. The planning stage includes identifying the needs and potential of UMKM Beauty Lily Jambangan Surabaya, as well as determining training and mentoring programs that are following the principles of Sharia business ethics. Next, the training and mentoring stage is carried out on an ongoing basis offline at the Beauty Lily Jambangan Surabaya location, by presenting material on the legal basis and principles of Sharia business ethics, as well as business examples from the Prophet Muhammad SAW. The monitoring and evaluation phase is carried out to monitor the progress and results of the mentoring program. The activity results show that Beauty Lily Jambangan Surabaya leads to high enthusiasm and awareness in implementing Sharia business ethics in their business operations. MSMEs feel more motivated and committed to advancing their business by following Sharia principles, such as honesty, fairness, and helping others. The following service plan is to provide education and assistance in marketing products digitally following Sharia principles, as well as spreading a similar approach to other MSMEs. This program will continue to be monitored and evaluated on an ongoing basis to ensure the sustainability and successful implementation of Sharia business ethics among MSMEs.